Peak C-reactive protein levels do not predict 30-day mortality for bacteremia: A retrospective cohort study. Issue 1 (January 2020) - Kurisu, Ken; Yoshiuchi, Kazuhiro; Ogino, Kei; Okada, Yasusei; Oda, Toshimi
Abstract: Introduction: Although peak C-reactive protein (CRP) levels are correlated with the prognosis of some diseases, there have been no reports regarding the association between peak CRP levels and mortality in patients with bacteremia. The present study aimed to determine the association between peak CRP levels and prognosis in patients with bacteremia. Methods: This retrospective cohort study was conducted in a single tertiary hospital and included patients with bacteremia admitted to the emergency department from November 2012 to March 2017. Cox regression analysis was performed to examine the association between peak CRP levels and 30-day mortality. We also performed propensity score adjustment using potential confounding factors. Results: One hundred fifty-nine patients were included in the study. Peak CRP levels were significantly higher in the β-hemolytic streptococci ( P  = 0.001) and Streptococcus pneumoniae ( P  = 0.003) groups. The C-statistic of the multivariate logistic regression model for the propensity score was 0.88. For 30-day mortality, peak CRP levels >20 mg/dL did not show significance in the Cox regression analysis (hazard ratio, 0.866; 95% confidence interval, 0.489–1.537; P  = 0.62). Even after propensity score adjustment, no significance was noted (hazard ratio, 0.865; 95% confidence interval, 0.399–1.876; P  = 0.71). Conclusions: Peak CRP levels were not an independent predictor of mortality in patients with bacteremia in the emergency department. Clinicians should consider that patients with extremely high peak CRP levels do not necessarily have high mortality and vice versa.